The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8dt03734e
|View full text |Cite
|
Sign up to set email alerts
|

The lanthanide complexes of 2,2′-bipyridyl-6,6′-dicarboxylic dimethylanilides: the influence of a secondary coordination sphere on the stability, structure, luminescence and f-element extraction

Abstract: The secondary coordination sphere contributes to the stability of complexes, the extraction behaviour of the reagents and europium phosphorescence lifetimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The tert-butoxycarbonyl can be utilized instead of acetyl group, which allows for increasing the yield of N-ethylaminopyridines up to 70-90%. Am(III) separation [11,12]. Such ligands effectively separate the ions of 4f-and 5f-elements-a crucial step of modern closed (waste-free) nuclear fuel cycle.…”
Section: Scheme 2 Ethylation and Hydrolysis Of N-acetylaminopyridinesmentioning
confidence: 99%
See 4 more Smart Citations
“…The tert-butoxycarbonyl can be utilized instead of acetyl group, which allows for increasing the yield of N-ethylaminopyridines up to 70-90%. Am(III) separation [11,12]. Such ligands effectively separate the ions of 4f-and 5f-elements-a crucial step of modern closed (waste-free) nuclear fuel cycle.…”
Section: Scheme 2 Ethylation and Hydrolysis Of N-acetylaminopyridinesmentioning
confidence: 99%
“…One of the promising classes of compounds for both f-metal separation and luminescent devices is derivatives of 2,2 -bipyridyl-6,6 -dicarboxylic acid (BPDA), which are tetradentate ligands of N,N ,O,O -type. Previously, it has been shown that tertiary amides of 2,2 -bipyridyl-6, 6 -dicarboxylic acid bearing substituted N-ethylanilines are potential materials for Am(III) separation [11,12]. Such ligands effectively separate the ions of 4f-and 5f-elements-a crucial step of modern closed (waste-free) nuclear fuel cycle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations